2019
DOI: 10.3389/fmicb.2019.00387
|View full text |Cite
|
Sign up to set email alerts
|

Cave Actinobacteria as Producers of Bioactive Metabolites

Abstract: Recently, there is an urgent need for new drugs due to the emergence of drug resistant pathogenic microorganisms and new infectious diseases. Members of phylum Actinobacteria are promising source of bioactive compounds notably antibiotics. The search for such new compounds has shifted to extreme or underexplored environments to increase the possibility of discovery. Cave ecosystems have attracted interest of the research community because of their unique characteristics and the microbiome residing inside inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 86 publications
(72 reference statements)
3
81
0
Order By: Relevance
“…Other studies have shown that karst regions, i.e. regions where there is dissolution of the rocks, especially limestone, support the growth of many Streptomyces [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that karst regions, i.e. regions where there is dissolution of the rocks, especially limestone, support the growth of many Streptomyces [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Actinobacteria are a large group of high G+C Gram-positive bacteria (Barka et al, 2016) and the primary sources of bioactive compounds in particular commercially available antibiotics (Barka et al, 2016; Rangseekaew and Pathom-aree, 2019). So far, more than 10,000 different bioactive compounds have been identified from Actinobacteria (Martins et al, 2019), for example, vancomycins from Amycolatopsis orientalis , rifamycin from Amycolatopsis mediterranei , teicoplanin from Actinoplanes teichomyceticus , erythromycin from Saccharopolyspora erythraea , and gentamicin from Micromonospora purpurea (Lancini and Lorenzetti, 1993; Lazzarini et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, karst and cave environments have become popular areas for bioprospecting of antimicrobial Streptomyces [48,49]. Many of these areas are often associated with traditional medicine.…”
Section: Antibiotics From Cavesmentioning
confidence: 99%
“…Ancient texts suggest that a milky white exudate covering the surfaces of some caves called 'moonmilk' can heal multiple ailments [50]. Digging deeper, research has shown that moonmilk contains an abundance of Streptomyces that have antibacterial activity against a wide range of bacteria and fungi [49,50], and display strong growth suppression against multi-resistant Rasamsonia argillacea, a causative agent of invasive mycosis in cystic fibrosis and chronic granulomatous diseases [50]. Similar studies from the Hampoeil cave (dolomite with limestone) in Iran, linked to Palaeolithic habitation, revealed many antimicrobialproducing Streptomyces, as well as other species [51].…”
Section: Antibiotics From Cavesmentioning
confidence: 99%